Successful treatment of a large oral verrucous hyperplasia with photodynamic therapy combined with cryotherapy - Yu-Chao Chang; Chuan-Hang Yu (Elsevier, 2013)
Studies have shown that topical 5-aminolevulinic acid-mediated photodynamic therapy (ALA-PDT) can be used successfully for the treatment of oral verrucous hyperplasia (OVH). Studies have also demonstrated that cryotherapy could be used as a treatment modality for OVH lesions. In this case report, we tested the efficacy of topical ALA-PDT, combined with cryogun cryotherapy, for an extensive OVH lesion on the right buccal mucosa of a 65-year-old male areca quid chewer. The tumor was cleared after six treatments of combined topical ALA-PDT and cryogun cryotherapy. No recurrence of the lesion was found after a follow-up period of 18 months. We suggest that our combined treatment protocol may be effective in treating OVH lesions. The treatment course may be slightly shortened with this combined protocol and was well tolerated by the patient.